Além do riso de massa : humor, psicanálise e contemporaneidade - Ferreira, Samara Megume Rodrigues (2015)
The present study aimed to discuss, based on Freudian psychoanalysis, the relationship between laughter / humor, and culture and its configuration nowadays. This research is relevant due to the lack of studies on humor in the psychoanalytic field. We start from the realization of the contradiction between the creative and transforming power of humor in subjectivity and the massive use of comedy by the media. From study of jokes Freud inaugurates the incursion of psychoanalysis in the culture, revealing that the Witz is the most social of all unconscious formations. It is the symbolic realization of repressed desires, but unlike the symptom, lies within the mental health limits. Humor announces the existence of a face in a subject that supports the superego, and thus, it is a counterpoint to the guided ties in morality and guilt. The humor creates a social bond whose uniqueness is the affirmation (not denial) of the subject's wishes. The economic-social and historical changes of the last decades have produced significant changes in the culture, to the point of entertainment become fundamental to the social and individual life. Laughter has been used as instrument of seduction consumption. In this context, the humor might still have the revolutionary role described by Freud? What is the psychic statute of humor in contemporary times? Our hypothesis is that the role of humor is being dumped in favor of an apathetic and conformist laughter. The use of laughter as the handling device seems to undermine its libertarian character. In our theoretical path we crossed the first topic of the psychic apparatus by Witz's relationship with language, with repression, with the primary and secondary processes and the oniric elaboration. In the second topic the understanding of the Humor passed by the concepts of superego, ideal / idealization, mourning and castration. Then we investigated the laugher relation to the maintenance or disruption of certain social ties, entering its relationship with aesthetics (beautiful and the ugly) and with art. Humor is a sublimating process that amalgamates love and aggression, life and death. To think social bonds of humor we opened a dialogue with the history and philosophy. We found that laughter has always been transgressor, so sometimes been criticized, sometimes forbidden. In contrast, in contemporary times it happens to be stimulated. By the ideal of happiness, laughter becomes mandatory, and therefore sterile. We can conclude that, in link capacity, perhaps humor is still a small place of resistance, a waiver to hatred and violence.